2015
DOI: 10.1177/1541931215591371
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of Cognitive Task Analysis and Observational Research Data to Identify Deficiencies of Support for Situation Awareness

Abstract: Designers require insight into deficiencies of current support for situation awareness (SA) to be able to improve operators' SA through better system design. The current methods proposed in literature to gain insight into sources of SA errors are not suitable to identify deficiencies in the field of nautical operational network management. This paper proposes a structured approach for syntactic and semantic processing of cognitive task analysis (CTA) data and observational research data to identify deficiencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The starting point of developing new UI concepts was the set of deficiencies that we have identified in our previous work concerning SA (Van Doorn et al 2015. The objective was to generate proper underpinning theories for UI design concepts that can efficiently contribute to the enhancement of operators' SA.…”
Section: Interface Concept Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The starting point of developing new UI concepts was the set of deficiencies that we have identified in our previous work concerning SA (Van Doorn et al 2015. The objective was to generate proper underpinning theories for UI design concepts that can efficiently contribute to the enhancement of operators' SA.…”
Section: Interface Concept Developmentmentioning
confidence: 99%
“…Current systems, however, were not developed to support corridor traffic management. Several deficiencies of current systems for corridor traffic management have been identified (Van Doorn et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…They need to gain and maintain situation awareness (SA) based on large amounts of information about the corridor. Previous work, however, showed that current traffic management information systems do not sufficiently support users in perceptual and cognitive processes to interpret and understand the presented information (Van Doorn et al 2015, 2017b.…”
Section: Introductionmentioning
confidence: 99%